Effectiveness Of Learning Math "Spinning" Using Flashcards And Number Blocks For Students With Dyscalculia - Pambayun, Mutiara Wahyu Sekar; Minsih, Minsih (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The field of science that is considered an important basis for everyone is mathematics, because of its widespread application to various disciplines of knowledge. However, many students experience obstacles in following math lessons. Therefore, this study aims to examine the effectiveness of math learning with the "gasing" method using flashcards and number blocks for students with dyscalculia. This article is written using quantitative methods with a single subject experimental design using data collection techniques through purposive sampling techniques. The data collected are scores in the form of percentages. Data validity was tested using pretest and posttest. Data analysis was conducted using the Wilcoxon Signed-Rank Test. This study involved five students who were not in the same class, but still underwent the same intervention. The results showed that learning "spinning tops" using flashcards and number blocks in Baseline Phase A1 with a standard deviation of 10.95 and a standard error of the mean of 4.90. Then in Phase A2 it was seen to increase with a standard deviation of 8.94 and a standard error mean of 4.00. This is also seen in the bar graph which illustrates the increase in the average score of the A1 baseline phase pre-test and the A2 phase post-test after the experiment. The average pre-test score of 32 indicates the initial condition of students before receiving treatment then the average post-test score increased to 66 after students underwent learning with the "spinning top" method using flashcards and number blocks. Thus learning "gasing" using flashcards and number blocks has a significant effect in improving the math skills of students with dyscalculia.